Prepaid meter for electricity: Experiences from the user perspective of households in Germany - Wagner, Oliver; Wiegand, Julia (Momentum Quarterly, 2018)
Energy poverty is a phenomenon that can be observed more frequently in Germany in recent years, as in other countries of the global north. In this context, prepayment meters are increasingly used by energy companies as a tool to manage customers with arrears or frequent payment difficulties. The phenomenon of energy poverty in Germany is relatively young and thus the number of prepayment meters is still low. Subsequently the results of the first scientific survey of households with prepayment meters in Germany (in the federal state of North Rhine-Westphalia) are presented and analyzed. It shows that prepayment systems for electricity are associated with significant everyday changes for the affected households. Advantages are the continuation of energy supply despite existing electricity debts, a better cost control, and tapping energy-saving potential. Significant draw- backs include higher costs, the burden households have to recharge the meter, and supply disruptions take place on a larger scale but are not recorded. Despite that our survey shows a high level of satisfaction among the users. Nonetheless there is considerable need for regulation by the German legislator.